RETRACTED: Konstektualisasi Pendidikan Akhlak dan Karakter Menurut Imam Al Ghazali pada Pendidikan Islam di Indonesia - Mayalibit, Nabila; Masduki, Yusron (Asian Journal of Islamic Studies and Da'wah, 2023)
Character education is very important learning and must be instilled in children from an early age. Because character or morals become a personal description of that person. Indonesia is a country that instills character education in every school, be it Islamic schools or other public schools. In Indonesia, there are many character education that is implemented which adhere to the concept of character education formulated and developed by Imam Al Ghazali. Until now, the concept developed by him is still considered relevant to face the times.